Rekonstruksi Nalar Islam: Tinjauan Problematis Relevansi Teks dan Konteks - Hidayat, Wildan (Analisis: Jurnal Studi Keislaman, 2017)
Religion descends on the will of God, but understanding and trying to realize religion is up to the object of religion itself, namely human beings. It was at this point that the science of religion was born, which was entirely human and dependent on the mastery of human knowledge. Religion is sacred, holy and perfect, but understanding religion is human, imperfect and worldly. The constant is religion itself (al-diin nafsuh), while the knowledge or understanding of religion (al-ma'rifah al-diniyyah) is temporal and will change. Context is often overlooked by a system of understanding that is brutally adhered to by Islamic reasoning now, so to return the text to something sacf li kulli zaman wan there needs to be a problematic review and 're-reading' to get 'new understanding' of modern Islam. Ushul Juris prudence which is a reaction/ response to the problem of the system as well as the doctrine of 'dirty' politics and disputes of ahl-Ra'yi and ahl-Hadīst about the meaning of texts in the modern era is required to be able to provide solutions to stagnation of Islamic law. Ushul Jurisprudence is not only as a ‘device’ reader of the text of the Qur'an and al-Sunnah but also acts as ‘bidder’ for a new understanding situation. However, the condition of the Ushul Fikih reading room as a level of Islamic religious law has limited methodology so that it cannot cover all aspects of understanding. This is where the author feels the need to bring up the offer and continuation of reconstruction related to the understanding of religion, especially the reconstruction of the Islamic Jurisprudence, so that the plurality of understanding of the sacred Islam will not only be a brutal understanding (madzhabi taqlidi) but the embodiment of methodology in understanding religion is really real.